2018
DOI: 10.1016/j.bbr.2018.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Incubation of feeding behavior is regulated by neuromedin U receptor 2 in the paraventricular nucleus of the hypothalamus

Abstract: A diet of energy-dense food, characterized mainly as a high-fat diet, leads to a persistent excessive consumption defined as overeating. According to the National Institute of Health, more than 2 in 3 adults in the United States are overweight or obese, straining our healthcare system with epidemic proportions. Diets that include abstaining from high-fat foods, ironically, result in an increase in motivation and craving for said high-fat foods, defined as an incubation effect because the behavior aids in devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
(82 reference statements)
0
5
0
Order By: Relevance
“…Rats responded in ten 6-hr daily sessions for intravenous cocaine and a tone+light cue. examined incubation of craving for complex foods and fats (e.g., standard or high-fat food pellets; Darling et al, 2016;Dingess et al, 2017;McCue, Kasper, & Hommel, 2019). * Indicates significant difference from Day 1, p < .05.…”
Section: Incubation Of Cravingmentioning
confidence: 99%
See 3 more Smart Citations
“…Rats responded in ten 6-hr daily sessions for intravenous cocaine and a tone+light cue. examined incubation of craving for complex foods and fats (e.g., standard or high-fat food pellets; Darling et al, 2016;Dingess et al, 2017;McCue, Kasper, & Hommel, 2019). * Indicates significant difference from Day 1, p < .05.…”
Section: Incubation Of Cravingmentioning
confidence: 99%
“…Serotonin 2C receptors have been associated with appetite (Halford & Harrold, 2012). In contrast to these negative effects, using a molecular manipulation, McCue et al (2019) reported that knockdown of neuromedin U receptor 2 in the paraventricular nucleus of the hypothalamus prevents incubation of high-fat food craving. These densities are hypothesized to be recruited to "stabilize" synapses and have been related to memory formation and retention (Slaker et al, 2018).…”
Section: Molecular Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…NAc expression of NMU and NMUR2 in both sensitized and non-sensitized animals was quantified by RT-PCR (7500 Fast Real Time PCR system, Applied Biosystems). Rats were euthanized with Ketamine/Xylazine (Benzon et al, 2014 ; McCue et al, 2018 ), and the NAc was microdissected on ice (Paxinos and Watson, 2007 ). NAc tissue was homogenized, RNA was extracted (74104, Qiagen, Germantown, MD, USA) and converted to cDNA (170-8891, BioRad, Hercules, CA, USA).…”
Section: Methodsmentioning
confidence: 99%